VGluT3 BNST neurons transmit GABA and restrict sucrose consumption - Annie Ly; Rachel Karnosky; Emily D. Prévost; Hayden Hotchkiss; Julianne M. Pelletier; Robert L. Spencer; Christopher P. Ford; David H. Root (Molecular Metabolism, 2025)
Objective: The bed nucleus of the stria terminalis (BNST) is involved in feeding, reward, aversion, and anxiety-like behavior. We identify BNST neurons defined by the expression of vesicular glutamate transporter 3, VGluT3. Methods: A combination of in situ hybridization, tract tracing, ex vivo whole-cell electrophysiology, in vivo recording, optogenetic, and behavioral approaches were used. Results: VGluT3 neurons were localized to anteromedial BNST, were molecularly distinct from accumbal VGluT3 neurons, and co-express vesicular GABA transporter (VGaT). BNST VGluT3 neurons projected to arcuate nucleus (ARC) and paraventricular nucleus of the hypothalamus (PVN), regions critical for feeding and homeostatic regulation. Most single BNST VGluT3 neurons projected to either PVN or ARC and a subset projected to both. BNST VGluT3 neurons functionally transmit GABA to both ARC and PVN, with rare glutamate co-transmission to ARC. In vivo, VGluT3 BNST neurons showed greater neuronal activity in response to sucrose consumption while sated compared with fasted. When fasted, optogenetic stimulation of BNST VGluT3 neurons decreased sucrose consumption using several stimulation conditions but not when stimulation occurred prior to sucrose access, suggesting that BNST VGluT3 activation concurrent with consumption in the fasted state reduces feeding. BNST VGluT3 activation had no effect on anxiety-like behavior in several paradigms (novelty-suppressed feeding, open field, and elevated zero maze). BNST VGluT3 activation also did not result in real-time place preference or aversion. Conclusions: We interpret these data such that VGluT3 BNST neurons represent a unique cellular population within the BNST that provides inhibitory input to hypothalamic regions to decrease sucrose consumption.